PARENTING STYLES AND QUR’ANIC LEARNING MOTIVATION: BRIDGING FAMILY ROLES AND STUDENT ACHIEVEMENT - Agustian; Listian Indriyani Achmad (EDUCATIONE, 2025)
Children are a trust that must be honored and granted their rights, particularly the right to education, with parents serving as the child's first educators. This study aims to analyze the relationship between parenting styles and students' motivation in learning the Qur’an. Using a quantitative approach with a descriptive-correlational method, the study involved 38 fifth-grade students of SD Islam Salman Al Farisi Bekasi and their parents. Purposive sampling was applied, along with validity and reliability testing of the instruments. Results showed: 1) Parenting style was classified as moderately democratic (mean = 87.84), 2) Students’ motivation in learning the Qur’an was categorized as moderate with dominant extrinsic motivation (mean = 64.76), and 3) A very strong correlation was found between parenting style and learning motivation (r = 0.825; R² = 68.1%). These findings highlight the vital role of parental involvement in fostering children's motivation to learn the Qur’an from an early age within the family environment.